2020
DOI: 10.1101/2020.02.06.936641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lateral gene transfer drives metabolic flexibility in the anaerobic methane oxidising archaeal familyMethanoperedenaceae

Abstract: Anaerobic oxidation of methane (AOM) is an important biological process responsible for controlling the flux of methane into the atmosphere. Members of the archaeal family Methanoperedenaceae (formerly ANME-2d) have been demonstrated to couple AOM to the reduction of nitrate, iron, and manganese. Here, comparative genomic analysis of 16 Methanoperedenaceace metagenome-assembled genomes (MAGs), recovered from diverse environments, revealed novel respiratory strategies acquired through lateral gene transfer (LGT… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Methanoperedens”, GoM Arc I (also known as AAA), was recently described as an anaerobic ethane degrader, and contains two genera “ Candidatus Argoarchaeum” (15, 21) and the thermophilic “ Candidatus Ethanoperedens”(28). These clades are not specifically considered in the present work as they do not appear to be marine methanotrophs, and have been extensively discussed in a recent study (29).…”
Section: Resultsmentioning
confidence: 99%
“…Methanoperedens”, GoM Arc I (also known as AAA), was recently described as an anaerobic ethane degrader, and contains two genera “ Candidatus Argoarchaeum” (15, 21) and the thermophilic “ Candidatus Ethanoperedens”(28). These clades are not specifically considered in the present work as they do not appear to be marine methanotrophs, and have been extensively discussed in a recent study (29).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that some Ca . Methanoperedens archaea are genetically equipped to use As(V) as an electron acceptor as many of the available genomes encode for arsenate reductase (Arr) (Glodowska et al, 2022; Leu, 2020). However, until now there is a lack of laboratory studies linking the presence of arr genes with actual As(V) reduction and CH 4 oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…The Ca. Methanoperedenaceae (previously named ANME-2d) are also closely related to ANME-2a/b in the phylogenetic tree, but they are able to live without partner bacteria and are largely derived from freshwater habitats 16 . The ANME-3 clade is usually dominant in methane-rich mud volcanoes 17 .…”
mentioning
confidence: 99%